2023
DOI: 10.4014/jmb.2212.12041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Euglena gracilis on Enhancing Immune Responses in RAW264.7 Cells and a Cyclophosphamide-Induced Mouse Model

Abstract: In this study we evaluated the immune-enhancing effects of β-glucan, the main component of Euglena gracilis ( Euglena ), and Euglena on inflammatory factor expression in RAW264.7 macrophages and ICR mice with cyclophosphamide-induced immunosuppression. Macrophages were treated with β-glucan or Euglena for 48 h. The β-glucan and Euglena groups exhibited higher levels of inducible nitric oxide synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Euglena and β-glucan have been shown to improve health by enhancing immunity, inhibiting atopic dermatitis, and modulating gut microbial composition [ 6 , 7 ]. In vitro, in vivo, and clinical trial studies have demonstrated that Euglena and β-glucan activate the immune system by releasing cytokines and inducing the immune cells such as natural killer cells or T lymphocytes [ 8 - 10 ]. They also activate the production of TNF-alpha in macrophages and modulate the expression of various cytokines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Euglena and β-glucan have been shown to improve health by enhancing immunity, inhibiting atopic dermatitis, and modulating gut microbial composition [ 6 , 7 ]. In vitro, in vivo, and clinical trial studies have demonstrated that Euglena and β-glucan activate the immune system by releasing cytokines and inducing the immune cells such as natural killer cells or T lymphocytes [ 8 - 10 ]. They also activate the production of TNF-alpha in macrophages and modulate the expression of various cytokines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, in vivo, and clinical trial studies have demonstrated that Euglena and β-glucan activate the immune system by releasing cytokines and inducing the immune cells such as natural killer cells or T lymphocytes [ 8 - 10 ]. They also activate the production of TNF-alpha in macrophages and modulate the expression of various cytokines [ 10 ]. Although they are known for their antitumor, anti-inflammatory, and antiallergic effects, the detailed genetic immune mechanisms involved remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%